The effectiveness of biopolymers application for cryopreservation of the fragments of convoluted seminiferous tubules of prepubertal rat’s testis - Volkova, N. O.; Yukhta, M. S.; Chernyschenko, L. G.; Stepaniuk, L. V.; Sokil, L. V.; Goltsev, A. M. (Cell and Organ Transplantology [Internet]. 31May2019 [cited 30Nov.2022];7(1)., 2019)
Today, transplantation of cryopreserved fragments of immature testis is a non-alternative method of preserving the fertility of pre-adolescent patients who undergo cytotoxic therapy. The purpose of the study is to compare the effectiveness of the use of biopolymers (bovine serum albumin and fibrin gel) as the bases of cryoprotective media at low temperature preservation of the fragments of the convoluted seminiferous tubules of prepubertal rats’ testis. Materials and methods. Convoluted seminiferous tubules of prepubertal rats’ testis (75 ± 3 mg and 6-8 mm3), after a 30-minute exposure at 4 °C in cryoprotective media based on Hanks’ solution with 50 g/L of bovine serum albumin (BSA) or fibrin gel (FG) supplemented with 0.6 M DMSO or 0.7 M glycerol, were cryopreserved according to the program: 1 °C/min to -8 °C; stop for 10 minutes; 10 °C/min to -70 °C; stored in liquid nitrogen. After thawing, the histological structure was evaluated and the metabolic activity of the spermatogenic epithelium cells was determined. Results. According to the results of the histological study, there was a positive tendency of FG application, which had the maximum expressiveness in combination with 0,7 M glycerol. In this case, 68.8 ± 15.7 % of cell nuclei remained morphologically intact, and changes in the spermatogenic epithelium were slightly pronounced. The metabolic activity of the rats’ seminiferous convoluted tubules cells after freezing and thawing remained at a significantly higher level when using FG in combination with 0.6 M DMSO than with 0.7 M glycerol compared to the corresponding cryoprotectant based on the Hanks’ solution with BSA. Conclusions. The use of fibrin gel in the protocols of cryopreservation provide to preserve the histological structure and metabolic activity of the spermatogenic epithelium.
Volkova N, Yukhta M, Chernyschenko L, Stepaniuk L, Sokil L, Goltsev A. The effectiveness of biopolymers application for cryopreservation of the fragments of convoluted seminiferous tubules of prepubertal rat’s testis. Cell and Organ Transplantology. 2019; 7(1):12-17. doi:10.22494/cot.v7i1.92
Keywords: testicular tissue; prepubertal age; dimethyl sulfoxide; glycerol; cryopreservation; bovine serum albumin; fibrin gel